THE INFLUENCE OF SOCIAL MEDIA AND MARKETING CONTENT ON PURCHASE INTENTION FOR NUFACE PRODUCTS ON TIKTOK SHOP: A CASE STUDY OF STUDENTS AT AS-SYAFI'IYAH ISLAMIC UNIVERSITY - Chusnah, Chusnah; Sugiana, Ugi (Fakultas Ekonomi dan Bisnis Universitas Islam As-Syafi'iyah, 2025)
This study aims to test